A case series of CMV infections in infants and its inoppurtune immuno-hematological manifestations - Abhilasha Sampagar; Pratima D. Patil; Taiseenub Patel; Shiv Dubey (Elsevier, 2022)
Congenital cytomegalovirus (CMV) infection is rampant viral disease, one of the commonest non-genetic cause for neurodevelopmental delay which is often under diagnosed. Leukemoid reaction, Hemophagocytic Lymphohistiocytosis (HLH) and autoimmune cytopenias are rare hematological manifestations of CMV infection. There is paucity of literature regarding hematological manifestation in CMV infection. Here we present four cases of CMV infection with different hematological findings where early diagnosis and prompt intervention resulted in good outcome.